The effect of modified Rusie Dat Ton training on functional physical fitness in obese older women - วิดจายา วารี; วงษ์วัฒนพงษ์ ธนารักษ์; อัจจิมาพร อมรพันธ์ (Journal of Medicine and Health Sciences, 2019)
Abstract Recently, Thailand has been faced with increased number of older adults and obesity. These conditions can affect physical degeneration. However, an exercise can postpone regeneration and improve physical fitness. Rusie Dat Ton which is appropriate for older adults, it is still one type of exercise which has a few studies. Therefore, the aim of this study was to investigate the effect of 8-week modified Rusie Dat Ton training on functional physical fitness in obese older women. Eleven participants participated in this study which their mean ages, mean body mass index, mean body fat and mean waist to hip ratio were 63.63 ± 0.97 years, 26.30 ± 0.58 kg/m2, 37.36 ± 0.70 %, and 0.92 ± 0.07, respectively. They performed the modified Rusie Dat Ton program for 60 minutes, 3 times/week throughout 8 weeks. Functional physical fitness (functional reach test, sit and reach test, 30-second chair stand test, 8-foot up and go test, six-minute walk test) were measured at baseline (0-week), 4th-week, 8th-week, respectively. One-way analysis of variance with repeated measurement (ANOVA) is used for a statistical analysis. The results demonstrated that all functional physical fitness parameters after 8th-week training were significant differences (p ≤ 0.05) when compared with the baseline. In addition, functional reach test and 30-second chair stand test were significant difference (p ≤ 0.05) when compared between baseline with 4th-week, and 4th-week with 8th-week, respectively. In conclusion, modified Rusie Dat Ton can be used as an alternative exercise and lead to obtain the beneficial physical performance and safety for obese older women.